Enhanced freshwater production from waste/brackish/saline water in remote arid areas using specially designed coolant plates - Bahar, Rubina; Ariff, Tasnim Firdaus (2016)
The work aims to improve the overall production from a small scale freshwater supply system by implementing channelled coolant plates instead of the traditionally used flat plates. The coolant plate is used in a special type of water purification system which is called Air Gap Membrane Distillation (AGMD). It is a low-temperature membrane process where the vapour from the waste/saline water is generated due the partial pressure difference across a membrane. The partial pressure difference is created by maintaining a temperature difference across the membrane . The vapour travels through the hydrophobic membrane pores and gets condensed on the cooler side on a condensing (coolant) plate. If the coolant plate can be designed and manufactured with channels, it will impose a "fin"-effect on the coolant side which subsequently will accelerate condensation and thus make more room for more vapour to come in. It will influence the total partial pressure difference to enhance the production. As AGMD units are compact and portable, and does not need high pressure/temperature, it seems to be a promising technology for water supply in the arid and remote areas with water scarcity. Improvement of this system by implementing channelled coolant plates will aid in the productivity.